Discussion (Scottish Historical and Archaeological Internet Reports, 2009)
A building which exemplifies the suggested appearance of the Brunary Burn structures '“ drystone walling with a hipped thatched roof '“ is preserved as the 'Cottars' House' at Auchindrain Museum near Inverary. One possible interpretation of these sites is that they were a response to the growing kelp industry in the early 19th century, with eventual economic slowdown and population decrease witnessed in the 1840s. As a direct result of the clearances, famine and emigrations, these houses were abandoned and left to fall to ruin.